Jasmonic Acid Modulates the Physio-Biochemical Attributes, Antioxidant Enzyme Activity, and Gene Expression in Glycine max under Nickel Toxicity - Sirhindi, Geetika; Mir, Mudaser Ahmad; Abd-Allah, Elsayed Fathi; Ahmad, Parvaiz; Gucel, Salih (Frontiers in Plant Science, 2016)
In present study, we evaluated the effects of Jasmonic acid (JA) on physio-biochemical attributes, antioxidant enzyme activity and gene expression in soybean (Glycine max L.) plants subjected to nickel (Ni) stress. Ni stress decreases the shoot and root length and chlorophyll content by 37.23%, 38.31% and 39.21% respectively over the control. However, application of JA was found to improve the chlorophyll content and growth of Ni-stressed seedlings in terms of root and shoot length. Plants supplemented with Jasmonate restores the chlorophyll fluorescence, which was disturbed by Ni stress. The present study demonstrated increase in proline, glycinebetaine, total protein and total soluble sugar (TSS) by 33.09%, 51.26%, 22.58% and 49.15% respectively under Ni toxicity as compared to control. Supplementation of JA to Ni stressed plants further enhanced the above parameters. Ni stress increases hydrogen peroxide (H2O2) by 68.49%, lipid peroxidation (MDA) by 50.57% and NADPH oxidase by 50.92% over the control. Supplementation of JA minimizes the accumulation of H2O2, MDA and NADPH oxidase, which helps in stabilization of biomolecules. The activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX) increases by 40.04%, 28.22%, 48.53% and 56.79% respectively over the control in Ni treated seedlings and further enhancement in the antioxidant activity was observed by the application of JA. Ni treated soybean seedlings showed increase in expression of Fe-SOD by 77.62%, CAT by 15.25%, POD by 58.33% and APX by 80.58% over the control. Nevertheless, application of JA further enhanced the expression of the above genes in the present study. Our results signified that Ni stress caused negative impacts on soybean seedlings, but, co-application of JA facilitate the seedlings to combat the detrimental effects of Ni through enhanced osmolytes and osmoprotectants, antioxidant enzyme activity and gene expression.